Machine Learning - Mellouk, Abdelhamid; Chebira, Abdennacer (IntechOpen, 2009)
Machine Learning can be defined in various ways related to a scientific domain concerned with the design and development of theoretical and implementation tools that allow building systems with some Human Like intelligent behavior. Machine learning addresses more specifically the ability to improve automatically through experience.